Resurgent and delayed malaria - Greenwood, B; Zongo, I; Dicko, A; Chandramohan, D; Snow, RW; Ockenhouse, C (BioMed Central, 2022)
The populations of moderate or highly malaria endemic areas gradually acquire some immunity to malaria as a result of repeated exposure to the infection. When this exposure is reduced as a result of effective malaria control measures, subjects who benefitted from the intervention may consequently be at increased risk of malaria if the intervention is withdrawn, especially if this is done abruptly, and an effective malaria vector remains. There have been many examples of this occurring in the past, a phenomenon often termed ‘rebound malaria’, with the incidence of malaria rebounding to the level present before the intervention was introduced. Because the main clinical burden of malaria in areas with a high level of malaria transmission is in young children, malaria control efforts have, in recent decades, focussed on this group, with substantial success being obtained with interventions such as insecticide treated mosquito nets, chemoprevention and, most recently, malaria vaccines. These are interventions whose administration may not be sustained. This has led to concerns that in these circumstances, the overall burden of malaria in children may not be reduced but just delayed, with the main period of risk being in the period shortly after the intervention is no longer given. Although dependent on the same underlying process as classical ‘resurgent’ malaria, it may be helpful to differentiate the two conditions, describing the later as ‘delayed malaria’. In this paper, some of the evidence that delayed malaria occurs is discussed and potential measures for reducing its impact are suggested.